Small Cell Carcinoma of the Prostate in an Elderly Patient: A Case Report and Review of the Literature - Whitaker, Dale Alan (Rare Tumors, 2016)
Prostate cancer is the most common malignancy of men in the United States. Small-cell carcinoma (SCC), which typically presents as an aggressive lung malignancy, is a rare diagnosis within the setting of prostate cancer pathology. Due to its limited prevalence, little information regarding the treatment and prognosis of this disease in large populations is available. To date our current knowledge base is largely limited to case reports and retrospective case reviews. The mainstay of treatment for this particular histology most often involves a multimodality approach utilizing chemotherapy in conjunction with radiation therapy, androgen deprivation therapy, or prostatectomy. Here we present the case of an elderly 89-year-old Caucasian male who was diagnosed with SCC of the prostate. Despite proceeding with a course of definitive radiotherapy, the patient experienced rapid progression of disease and ultimately elected to discontinue radiation therapy and receive hospice care.